Knowledge, attitudes, and practices among livestock owners, traders, and slaughterhouse inspectors in Cameroon reveals marginal understanding of livestock and human brucellosis - Dada, Charles Olivier Gomsu; Laine, Christopher G.; Guela, Gaelle Kamdjo; Gontao, Pierre; Garcia-Gonzalez, Daniel; Mouiche, Mohamed Moctar Mouliom; Wade, Abel; Arenas-Gamboa, Angela M. (Frontiers in Veterinary Science, 2026)
IntroductionBrucellosis, a zoonotic disease, significantly impacts animal and public health, as well as agricultural economies reliant on livestock. This disease is endemic in many regions worldwide, with the highest risk of infection in sub-Saharan Africa. However, the true extent of the disease in Africa remains largely unknown. In Cameroon, a country in western Central Africa, Brucella abortus is endemic in livestock, and the bacteria have been found in milk sold at community markets throughout the country.MethodsThis study aims to understand the knowledge, attitudes, and biosecurity practices of those closely working with animals throughout the livestock supply chain from farm to slaughter. Three KAP surveys were conducted among livestock owners, traders, and slaughter facility inspectors at live markets and abattoirs in the Far North, North, and West regions of the country due to their pivotal importance in the national and international supply chain.ResultsFindings reveal minimal understanding of brucellosis and limited biosecurity practices across the network of owners, traders, and abattoir inspectors.DiscussionThe lack of understanding and deficiencies in health infrastructure likely contribute to the persistence of B. abortus as endemic in the country and region as a whole. This study provides insights into animal and public health risks and aims to aid policymakers in developing interventions to reduce the disease burden.